Transtorno do espectro autista e diagnóstico diferencial do atraso de fala na infância: uma revisão da literatura - Guilherme de Araújo Baptistello; Camila Haas; Victória Baú Rabello; Bernardo Penteado Favero; Gabriele Eckerdt Lech; Carolina Carlesso Freitas; Carolina Moronte Sturmer; André Rumi Steinbruch; Luis Felipe Pilar Gomes; Gabriela Santos Rocha; Camila Santos Halal (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: This article describes the main conditions in the differential diagnosis of speech delay in childhood, with emphasis on the updated diagnostic criteria to differentiate between neurodevelopmental disorders, such as autism spectrum disorders, and other possible conditions. METHODS: This non-systematic review of the literature was performed based on updated diagnostic criteria and definitions. RESULTS: Speech delays are a common symptom in children with neurodevelopmental disorders, often associated with autism spectrum disorders. However, there is a range of conditions in which speech delay is a symptom that must be considered in differential diagnosis, including other neurodevelopmental disorders, hearing loss, and language disorders. CONCLUSION: Pediatricians play an important role in the assessment, investigation, and management of children with speech delays. Therefore, they should be familiar with the expected neurodevelopmental milestones, the warning signs of developmental disorders including language disorders, and the diagnostic criteria for the most prevalent conditions.